Novel Insights into Causal Effects of Lipid and Lipid-Lowering Targets with Autoimmune Thyroid Disease: A Mendelian Randomization Study - Su C; Tian J; He X; Chang X; Wang G; Liu J (ImmunoTargets and Therapy)
Chang Su, Juan Tian, Xueqing He, Xiaona Chang, Guang Wang, Jia Liu Department of Endocrinology, Beijing Chao-Yang Hospital, Capital Medical University, Beijing, 100020, People’s Republic of ChinaCorrespondence: Guang Wang; Jia Liu, Department of Endocrinology, Beijing Chao-Yang Hospital, Capital Medical University, NO. 8, Gongti South Road, Chaoyang District, Beijing, 100020, People’s Republic of China, Tel +8610-85231737 ; +8610-85231710, Email drwg6688@126.com; liujia0116@126.comBackground: Dyslipidemia has been implicated in the pathogenesis of several diseases, including thyroid dysfunction and immune disorders. However, whether circulating lipids and long-term use of lipid-lowering drugs influence the development of autoimmune thyroid disease (AITD) remains unclear. This study aims to evaluate the effects of lipid-lowering drugs on AITD and explore their potential mechanisms.Methods: Two-sample and two-step Mendelian randomization (MR) studies were performed to assess the causal relationships between circulating lipids (LDL-C, TC, TG, and ApoB) and seven lipid-lowering drug targets (ApoB, CETP, HMGCR, LDLR, NPC1L1, PCSK9, and PPARα) with AITD. Mediation analyses were conducted to explore potential mediating factors.Results: There was no clear causality between circulating lipids (ApoB, LDL-C, TC, and TG) and AITD (p > 0.05). ApoB inhibition is related to a reduced risk of autoimmune thyroiditis (AT) (OR = 0.462, p= 0.046), while PCSK9 inhibition is related to reduced Graves’ disease (GD) risk (OR = 0. 551, p = 0.033). Moreover, PCSK9 inhibition (OR = 0.735, p = 0.003), LDLR inhibition (OR = 0.779, p = 0.027), and NPC1L1 inhibition (OR = 0.599, p = 0.016) reduced the risk of autoimmune hypothyroidism (AIH). Mediation analysis showed that NPC1L1 inhibition and PCSK9 inhibition exerted effects on AIH through IL-4 and FGF-19 levels. And the effect of PCSK9 inhibition on GD through TNF-β levels.Conclusion: There was no clear causality between circulating lipids (ApoB, LDL-C, TC, and TG) and AITD. Lipid-lowering drug target gene inhibitors reduced the AITD risk by modulating inflammatory factors.Keywords: Mendelian randomization, drug targeting, thyroid autoimmune disease, lipid trait, inflammatory factors